PEMANFAATAN ELEKTRONIK AUDIT (E-AUDIT) DALAM MENINGKATKAN KINERJA PEMERIKSA PADA AUDITORAT UTAMA KEUANGAN NEGARA VI BADAN PEMERIKSA KEUANGAN RI - Irham Irham; Nurliah Nurdin; Bambang Supriyadi (Sekolah Tinggi Pariwisata Mataram, 2021)
Abstract This study aims to find out how the Role of the Utilization of the E-Audit in Improving the Performance of Auditors at the Main Auditorate of State Finance VI of the Supreme Audit Agency (BPK), analyze the causes of the use of the E-Audit not being maximized in improving the performance of examiners and the ideal E-Audit model. such as what can improve the performance of BPK examiners, this research uses qualitative designs are methods to explore and understand the meaning that comes from various problems, this qualitative process involves important efforts such as asking questions and procedures, collecting data that specifics of the participants and analyze the data. The purpose of this study is to obtain data and information that will be used for the preparation of the thesis, namely to analyze the Role of E-Audit Utilization in Improving Examiner Performance at the Main Auditorate of State Finance VI BPK The results showed that the cause of the use of the E-Audit not being maximized in improving examiner performance was influenced by several causes, as stated by Dale L. Goodhue & Ronald L. Thompson 1995, a technology information system model using 4 components, namely data quality, data locatability, ease of use. the operation and reliability of the system on the E-Audit has not fully supported users in carrying out audit tasks, for that it is necessary to develop an ideal model of the E-Audit that can improve examiner performance using the George M. Markas and James A.O'Brien (2008) model which using 5 components which are unity that influence each other, among others are Human Resources (HR), hardware resources (hardware), software resources (software), data resources and network resources Thus the recommended suggestions so that E-Audit can improve the performance of examiners are the development of professional human resources, the procurement of good hardware that can support computerization, the provision of good software and software that has high reliability, completeness of the audit database by expanding cooperation for data fulfillment and provision of adequate network resources, such as twisted-pair cable technology, coaxial cable, optical fiber, microwave, cellular and satellite wireless, as well as providing adequate network infrastructure so that the operation of the E-Audit can be utilized optimally